LOANWORDS AS AN EXPRESSIVE DEVICE IN LINA KOSTENKO’S POETIC TEXT - Ігнатьєва, Світлана; Цюп’як, Ірина (SWorldJournal, 2025)
The study explores borrowings as a means of expression in the poetic text of Lina Kostenko. The research focuses on the use of borrowings driven not so much by an active influence on the recipient but rather by a desire to modify their consciousness. It i